Loco-regional outcomes of adjusted breast radiotherapy with conventional fractionation after breast conserving surgery: De-escalation of whole breast irradiation dose - Kim, Sang-Won (Medicine (Baltimore), 2020)
We compared the cumulative incidence of ipsilateral breast tumor recurrence (IBTR) between 2 whole breast irradiation (WBI) dose range with conventional fractionation. We retrospectively reviewed 1122 patients who received WBI at 2 institutions between 2004 and 2012. One institution delivered WBI 41.4 to 45 Gy followed by boost 14 to 18 Gy (adjusted group), while the other delivered WBI 50 to 50.4 Gy followed by boost 10 Gy (standard group). The median follow-up period was 85 months. The 10-year cumulative incidence in all patients was 6.1% (95% confidence interval [CI]: 4.3%–8.4%) for IBTR and 3.0% (95% CI: 1.7%–4.8%) for regional recurrence. The 10-year cumulative incidence of IBTR was not significantly influenced by WBI dose (6.3% in the adjusted group vs 5.2% in the standard group, P = .136). Comparable IBTR rates between the 2 groups were observed regardless of clinical and pathological factors. The WBI dose was not significantly associated with the 10-year cumulative incidence of regional recurrence in these groups (3.5% in the adjusted group vs 0.5% in the standard group, P = .214). De-escalated WBI doses while intensifying tumor bed boost did not compromise local and regional outcomes compared to standard group.